Unimodular totally disconnected locally compact groups of rational discrete cohomological dimension one - Castellano, Ilaria; Marchionna, Bianca; Weigel, Thomas (Mathematische Annalen, 2025)
It is shown that a Stallings-Swan theorem holds in a totally disconnected locally compact (= t.d.l.c.) context (cf. Theorem B). More precisely, a compactly generated $${\mathcal{C}\mathcal{O}}$$-bounded t.d.l.c. group G of rational discrete cohomological dimension less than or equal to 1 must be isomorphic to the fundamental group of a finite graph of profinite groups. This result generalises Dunwoody’s rational version of the classical Stallings-Swan theorem to t.d.l.c. groups. The proof of Theorem B is based on the fact that a compactly generated unimodular t.d.l.c. group with rational discrete cohomological dimension 1 has necessarily non-positive Euler-Poincaré characteristic (cf. Theorem H).